2010
DOI: 10.1007/s10340-010-0339-9
|View full text |Cite
|
Sign up to set email alerts
|

Population growth of Pieris brassicae (L.) (Lepidoptera: Pieridae) on different cole crops under laboratory conditions

Abstract: The effect of different host plants including cabbage, cauliflower, mustard, radish, and broccoli on biological parameters of Pieris brassicae (L.) was studied in the laboratory at 28°C, 65 ± 5% RH and 12L:12D photoperiod. Duration of each life stage, longevity, the intrinsic rate of natural increase (r m ), net reproductive rate (R 0 ), mean generation time (T), doubling time (DT), and finite rate of increase (k) of the cabbage white butterfly on the different cole crops were estimated. Differences in fertili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 27 publications
2
27
0
Order By: Relevance
“…Elevated rate of reproduction, low transience rate and shorter development time of insects on a particular host points toward greater suitability of a host plant (Costa et al, 1991, a, b;Coudriet et al, 1985;Awmack and Leather, 2002;Hasan and Ansari, 2011). The gradual decreasing expectation of life was noticed as maximum on chili in the present investigation (Figure 1).…”
Section: Age Specific Survival Expectation and Mortalitysupporting
confidence: 56%
See 1 more Smart Citation
“…Elevated rate of reproduction, low transience rate and shorter development time of insects on a particular host points toward greater suitability of a host plant (Costa et al, 1991, a, b;Coudriet et al, 1985;Awmack and Leather, 2002;Hasan and Ansari, 2011). The gradual decreasing expectation of life was noticed as maximum on chili in the present investigation (Figure 1).…”
Section: Age Specific Survival Expectation and Mortalitysupporting
confidence: 56%
“…The instar duration of B. tabaci was differently affected by the various hosts during nymphal development (Campos et al, 2003;Bonato et al, 2007). Among the entire host plants, on which whitefly was reared, brinjal has shown superiority by documenting least mortality and shorter development time for immature stages of whitefly (Table 2) which indicates the suitability of brinjal as a host for immature development of whitefly (Awmack and Leather, 2002;Hasan and Ansari, 2011). Sharaf et al (1985) has also revealed the superiority of brinjal over other host plants for immature B. tabaci.…”
Section: Development and Survivorship Of Immature Stagesmentioning
confidence: 99%
“…Variations in behaviour could be related to chemical volatiles emitted by the plant interfering with host selection, and consequently with oviposition by the insect (Sharon et al 2009;Baldin and Beneduzzi 2010). A combination of chemical stimulants and deterrents determines the use of a plant species by ovipositing Pieris (Pieridae) females (Thompson and Pellmyr 1991;Hasan and Ansari 2011). Water-soluble compounds other than glucosinolates, appear to be primarily responsible for host choice in Pieris rapae (Renwick et al 1989), while specific cardenolides have been identified in crucifers as chemical deterrents to Pieris brassicae (Rothschild and Schoonhoven 1977).…”
Section: Discussionmentioning
confidence: 98%
“…Pieris brassicae (Lepidoptera: Pieridae ), which is commonly known as cabbage butterfly, affects cole crops and causes damage at all its growth stages 1 . This caterpillar feeds only on plants that releases glucosinolate, which is a characteristic feature of Brassicaceae that includes cabbages, cauliflower, and mustards 2 …”
Section: Introductionmentioning
confidence: 99%
“…This caterpillar feeds only on plants that releases glucosinolate, which is a characteristic feature of Brassicaceae that includes cabbages, cauliflower, and mustards 2 3 causing up to 40% yield loss per year 1 . Chemical insecticides are usually applied to control P. brassicae , but high tolerance to most insecticides and associated environmental problems have jeopardized their continued use 4 …”
Section: Introductionmentioning
confidence: 99%